NAP1L1 Functions as a Novel Prognostic Biomarker Associated With Macrophages and Promotes Tumor Progression by Influencing the Wnt/β-Catenin Pathway in Hepatocellular Carcinoma - Shen, Bingbing; Zhu, Wenjie; Liu, Xinyuan; Jiang, Jianxin (Frontiers in Genetics, 2022)
Hepatocellular carcinoma (HCC) is regarded as one of the most universal cancers in the world. Therefore, our study based on clinical, molecular mechanism and immunological perspectives for the purpose of analyzing how NAP1L1 affects the progression of HCC. Ground on GEO, ICGC and TCGA database, NAP1L1 were carried out from the four aspects survival analysis, clinical features analysis, univariate/ multivariate regression analysis and multiple GSEA analysis. The conclusion claimed that HCC patients who have owned higher expression levels of NAP1L1 had a poorer prognosis than these patients of lower expression levels, and NAP1L1 as an independent prognostic factor for HCC. In order to closely shed light on NAP1L1’s molecular mechanism promoting progression of HCC, GSEA tool was applied to complete GSEA analysis of the four datasets, and the results confirmed that NAP1L1 can promote HCC progression through regulating G2/M transition of the cell cycle and Wnt signaling pathway. Deeply understanding those mechanism, Western blot and flow cytometry were also performed in this study. The result of Western blot showed that NAP1L1 silencing led to down-regulation of CDK1 and β-catenin proteins; the result of flow cytometry was that Cell numbers in G2 phase were significantly increased when NAP1L1 silenced. Thus, we claimed that NAP1L1 may promote HCC progression by activating Wnt signaling pathway and promoting cell cycle G2/M transition. In addition, ground on GSE14520 and GSE76427 datasets, ICGC and TCGA databases, the correlated relation between NAP1L1 and immune cells were analyzed in HCC patients. At the same time, the TISIDB online database and the TIMER online database were testified the association between NAP1L1 and immune cells. Hence, the summary can be got that NAP1L1 was connected with a certain amount immune cells in which we can speculate that NAP1L1 may influence macrophages to promote HCC progression through some potential mechanisms.